2002
DOI: 10.1002/cbm.503
|View full text |Cite
|
Sign up to set email alerts
|

The treatment and security needs of patients in special hospitals: views of referring and accepting teams

Abstract: It may be more realistic to plan future services on the basis that only 9% of patients are misplaced, rather than the previous estimates that appear to have guided current policy. Patients detained under the legal category of psychopathic disorder present particular problems and there is a need to develop appropriate facilities at medium secure level. In the meantime, no patients should be admitted to high security without consultation with the catchment area service and a jointly agreed plan for future rehabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…CONSULTANT FORENSIC CLINICAL PSYCHOLOGIST -SERVICE LEAD quality of life flexible care, and therefore have more therapeutic impact on patients than is possible within the constraints of high-secure detention. Sayal and Maden (2002) also comment that the suggested figure of 20-30% of high-security patients that could be managed in a medium-secure setting is not based on objective criteria. They believe that the figure may be closer to nine per cent.…”
Section: Adrian G Westmentioning
confidence: 99%
“…CONSULTANT FORENSIC CLINICAL PSYCHOLOGIST -SERVICE LEAD quality of life flexible care, and therefore have more therapeutic impact on patients than is possible within the constraints of high-secure detention. Sayal and Maden (2002) also comment that the suggested figure of 20-30% of high-security patients that could be managed in a medium-secure setting is not based on objective criteria. They believe that the figure may be closer to nine per cent.…”
Section: Adrian G Westmentioning
confidence: 99%
“…Low risk of bias studies found a significantly lower TRS prevalence (28.4%, 95% CI 23.9-33.0) 7 , 16 , 25 , 26 , 32 , 33 , 36 , 38 - 40 , 48 , 50 , 53 , 54 , 57 , 58 , 60 , 62 , 66 , 67 , 69 , 71 than high risk of bias studies (44.35%, 95% CI 38.29-50·50) 8 , 27 - 31 , 34 , 35 , 37 , 41 - 47 , 49 , 51 , 52 , 55 , 56 , 59 , 61 , 63 - 65 , 68 , 70 (Q = 17.1, p < 0.0001). The results for individual scores and subgroup analyses across studies for each criterion and total scores are shown in , respectively.…”
Section: Resultsmentioning
confidence: 95%
“…This methodological feature may explain the unexpected finding that studies which considered intolerability-related treatment failure as TRS 25 - 27 , 29 , 31 , 34 , 35 , 40 , 41 , 47 , 53 , 57 , 64 , 65 , 69 reported a lower TRS prevalence than those that did not. 7 , 8 , 16 , 28 , 30 , 32 , 33 , 36 - 39 , 42 - 46 , 48 - 52 , 54 - 56 , 58 - 63 , 66 - 68 , 70 , 71 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations